6. SURGICAL TREATMENT OUTCOMES FOR MULTIDRUG-RESISTANT COMPLEX SOFT TISSUE INFECTIONS (Vietnam Journal of Community Medicine, 2024)
Introduction: Multidrug-resistant infections are an increasingly serious global healthcare issue, extending hospital stays and raising mortality rates. Complex soft tissue infections caused by multidrug-resistant organisms pose significant challenges for surgeons due to the limited antibiotic options available. Surgical debridement and, more recently, the advent of the Vacuum-Assisted Closure (VAC) system with irrigation have proven to be effective methods for treating complex infected wounds.Subjects - Research Methods: This is a case series study describing complex soft tissue infections caused by multidrug-resistant organisms, treated with surgical debridement combined with multiple rounds of VAC with irrigation at the Department of Orthopedic Trauma, University Medical Center Ho Chi Minh City.Results: From April 2024 to October 2024, we encountered 6 cases of complex soft tissue infections, all of which yielded cultures with multidrug-resistant organisms: Methicillin-resistant Staphylococcus aureus (MRSA), Klebsiella pneumoniae ESBL (-), AmpC (-), Pseudomonas aeruginosa, AmpC (-); and Enterobacter aerogenes ESBL (-), AmpC (-). One case involved sepsis and multiple soft tissue infections caused by Burkholderia pseudomallei. Patients underwent an average of 3.16 debridement surgeries and 3 VAC cycles, with 100% of cultures returning negative results and infection markers returning to normal. Four out of six cases had their wounds completely closed upon discharge, one case continued VAC therapy at home before returning for skin grafting, and one case remains under outpatient wound care.Conclusion: Surgical debridement combined with multiple rounds of VAC with irrigation proves to be an effective method for treating complex, multidrug-resistant soft tissue infections.
Keywords: Complex soft tissue infections; multidrug-resistant; surgical debridement; VAC system with irrigation